Answer:
(2,2)
Step-by-step explanation:
Given equations
x-3y=-4-------------------------------(1)
y=-3x+8.------------------------------(2)
Substitute 2 in 1. This means use the value of y in equation 1, to replace y
x-3(-3x+8)=-4------------------open brackets
x+9x-24=-4---------------------collect like terms
10x=-4+24
10x=20---------------------------divide by 10 both sides to get value of x
10x/10=20/10=2
x=2------------------------------use value of x in equation (2) to get value of y
y=-3x+8
y=-3(2)+8
y=-6+8=2
solutions
x=2, y=2
Answer:
D. 7/3
Explanation:
Y1 - Y2 / X1 - X2
9 - -5 / 6 - 0
9 + 5 / 6
14 / 6
7/3
Answer:
let me make it its equation I have done this but if this will work have a good day
0.4219 Approximately .
Also HIIII
We can suggest this equation.
(6x+x)+(6x+x)+110º+110º=360º
7x+7x+220º=360º
14x=360º-220º
14x=140º
x=140º/14
x=10º
Answer. x=10º